Eph/ephrin-mediated immune modulation: a potential therapeutic target - Giannopoulos, Konstantinos; Karikis, Ioannis; Byrd, Chad; Sanidas, Georgios; Wolff, Nora; Triantafyllou, Maria; Simonti, Gabriele; Vidva, Robinson; Koutroulis, Ioannis; Theocharis, Stamatios; Kratimenos, Panagiotis (Frontiers in Immunology, 2025)
Eph/ephrin signaling, a complex network of cell-cell interactions, plays a pivotal role in regulating various biological processes, including cell migration, proliferation, and adhesion. Dysregulation of this signaling pathway has been implicated in various types of cancer. In skin cancers such as squamous cell carcinoma, basal cell carcinoma, and malignant melanoma, Eph/ephrin signaling promotes tumor invasion and metastasis. Aberrant expression of Eph receptors and ephrin ligands can lead to increased cell motility, reduced cell adhesion, and enhanced angiogenesis. Furthermore, Eph/ephrin signaling can significantly impact the tumor microenvironment by modulating the infiltration and activation of immune cells, particularly T cells. Dysregulated Eph/ephrin expression can impair immune surveillance mechanisms, leading to immune evasion and tumor progression. For instance, certain ephrin ligands can inhibit T-cell activation and promote immunosuppressive conditions within the tumor microenvironment. Targeting Eph/ephrin signaling offers a promising therapeutic approach to combating skin cancer metastasis. By disrupting these signaling pathways, tumor cell invasion, angiogenesis, and immune evasion can be inhibited. This could lead to improved therapeutic outcomes for patients with skin cancer.